2011
DOI: 10.3758/s13428-011-0082-z
|View full text |Cite
|
Sign up to set email alerts
|

A simple 5-DoF MR-compatible motion signal measurement system

Abstract: The purpose of this study was to develop a simple motion measurement system with magnetic resonance (MR) compatibility and safety. The motion measurement system proposed here can measure 5-DoF motion signals without deteriorating the MR images, and it has no effect on the intense and homogeneous main magnetic field, the temporalgradient magnetic field (which varies rapidly with time), the transceiver radio frequency (RF) coil, and the RF pulse during MR data acquisition. A three-axis accelerometer and a twoaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Angle information is extracted by numerically integrating the angular velocity signals from the 2-axis gyrosensor by the Runge-Kutta method [24]. Various additional kinematic signals such as velocity and jerk can be calculated from acceleration and angle information [5,22].…”
Section: Physiological and Kinematic Signal Measurement Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Angle information is extracted by numerically integrating the angular velocity signals from the 2-axis gyrosensor by the Runge-Kutta method [24]. Various additional kinematic signals such as velocity and jerk can be calculated from acceleration and angle information [5,22].…”
Section: Physiological and Kinematic Signal Measurement Systemmentioning
confidence: 99%
“…Studies have observed autonomic nervous-system variables that change during driving, such as skin conductance level (SCL) and photoplethysmographic (PPG) readouts of heart activity, via sensors attached to the hands or wrists [20,21]. Moreover, ultra-high speed cameras and inertial measurement units (IMUs; i.e., sensors) are now available to extract variables related to human body movement while driving, measure the manipulation angle and acceleration of steering wheels, and measure the variability of accelerator-and brake-pedal [22,23].…”
Section: Introductionmentioning
confidence: 99%